Vestígios romanos encontrados na Rua Mouzinho da Silveira - Porto - Almeida, Carlos A. Brochado de; Almeida, Pedro Miguel D. Brochado de (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In Oporto city, Mouzinho da Silveira Street runs in a parallel tracing to the course of Vila River, at the western base of «Morro da Sé». There was found an Iron Age village with vestiges excessively registered. During this archaeological intervention it appeared remains belonging to a Low Empire construction and also High Empire’s ceramics, along with others belonging to the High Middle Age. Above them, since the XVIIth century, other ocupations were recorded. The roman remains are chronological similar to those already known from «Casa do Infante», Ribeira Square and D. Hugo Street.